Immunoregulatory framework and the role of miRNA in the pathogenesis of NSCLC – A systematic review - Samarth, Nikhil; Gulhane, Pooja; Singh, Shailza (Frontiers in Oncology, 2022)
With a 5-year survival rate of only 15%, non-small cell lung cancer, the most common kind of lung carcinoma and the cause of millions of deaths annually, has drawn attention. Numerous variables, such as disrupted signaling caused by somatic mutations in the EGFR-mediated RAS/RAF/MAPK, PI3K/AKT, JAK/STAT signaling cascade, supports tumour survival in one way or another. Here, the tumour microenvironment significantly contributes to the development of cancer by thwarting the immune response. MicroRNAs (miRNAs) are critical regulators of gene expression that can function as oncogenes or oncosuppressors. They have a major influence on the occurrence and prognosis of NSCLC. Though a myriad number of therapies are available and many are being clinically tested, still the drug resistance, its adverse effect and toxicity leading towards fatality cannot be ruled out. In this review, we tried to figure out the missing links in between perturbed EGFR signaling, miRNAs favouring tumorigenesis and the autophagy mechanism. While connecting all the aforementioned points multiple connections were set, which can be targeted in order to combat NSCLC. Here, we tried illuminating designing synthetically engineered circuits with toggle switches that might lay a platform for better therapeutic paradigm.